(untitled) (Universal International Scientific Journal, 2026)
This article is based on the fact that the digital society is causing fundamental changes in all aspects of human life, in the system of morals and values. It is explained that due to the rapid development of technologies and the widespread use of the Internet, communication, social relations and moral norms between people are being reshaped. Parenting in a digital environment: psychological and ethical approaches are discussed.